2002
DOI: 10.1136/jnnp.72.5.661
|View full text |Cite
|
Sign up to set email alerts
|

Sleep symptoms and polysomnographic architecture in advanced Parkinson's disease after chronic bilateral subthalamic stimulation

Abstract: Objective: To evaluate the sleep symptoms and polysomnographic architecture in advanced Parkinson's disease after chronic bilateral subthalamic stimulation (STN-DBS). Methods: Sleep was studied in 11 patients (six women and five men; mean (SD) age 63.6 (7.8) years) who underwent STN-DBS. Subjective sleep evaluation was assessed by clinical sleep interview and the Pittsburgh sleep quality index (PSQI) questionnaire, and sleep architecture by polysomnography with audiovisual recording. Nocturnal mobility was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
91
1
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(102 citation statements)
references
References 15 publications
4
91
1
6
Order By: Relevance
“…Polysomnographic sleep parameters disturbances associated with PD are poor sleep efficiency, a decrease in the quantity of N3 sleep, and R sleep 29 . In our patients, total N3 sleep was low but was not considered a clinical significant finding due to the fact that N3 diminishes with age.…”
Section: Discussionmentioning
confidence: 99%
“…Polysomnographic sleep parameters disturbances associated with PD are poor sleep efficiency, a decrease in the quantity of N3 sleep, and R sleep 29 . In our patients, total N3 sleep was low but was not considered a clinical significant finding due to the fact that N3 diminishes with age.…”
Section: Discussionmentioning
confidence: 99%
“…Three Class III studies using PSG found an improvement in sleep quality following DBS of the STN. [32][33][34] In one study, total sleep time increased from a mean of 281 minutes before DBS to a mean of 360 minutes after DBS (with DBS on), an improvement of 28%. 32 Other studies showed a significant decrease in the arousal index from 18.0 to 11.2 (38%), 33 and total sleep efficiency increased by a mean of 36%.…”
mentioning
confidence: 99%
“…[32][33][34] In one study, total sleep time increased from a mean of 281 minutes before DBS to a mean of 360 minutes after DBS (with DBS on), an improvement of 28%. 32 Other studies showed a significant decrease in the arousal index from 18.0 to 11.2 (38%), 33 and total sleep efficiency increased by a mean of 36%. 36 A Class I study found that levodopa/carbidopa administered at bedtime decreased the frequency of spontaneous movements in bed from 43/night to 28 -33/night.…”
mentioning
confidence: 99%
“…Response of RLS symptoms in PD patients following STN DBS and pallidotomy has been reported (5,10,13). However, polysomnography studies measuring the PLM index in PD patients who have undergone STN DBS have been variable (2,4,6). The marked reduction in contralateral movements and nearly immediate reversibility of the observed effect in this patient with intraoperative stimulation suggest that perhaps PLM may be potentially responsive to GPi DBS.…”
Section: Discussionmentioning
confidence: 76%